2020
DOI: 10.1186/s12864-020-6639-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous circadian time genes expressions in the liver of mice under constant darkness

Abstract: Background: The circadian rhythms regulate physiological functions and metabolism. Circadian Time (CT) is a unit to quantify the rhythm of endogenous circadian clock, independent of light influence. To understand the gene expression changes throughout CT, C57BL/6 J mice were maintained under constant darkness (DD) for 6 weeks, and the liver samples were collected starting at 9:00 AM (CT1), and every 4 h in a 24-h cycle (CT5, CT9, CT13, CT17 and CT21). Total RNA was extracted and subjected to RNA-Seq data (depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…So, our results suggest that there are two subgroups of circadian genes: one group with oscillation behavior both at light-dark condition and continuous light are only regulated by core clock mechanism, while the other group with continuous light-specific oscillation are regulated by core clock mechanism and also by another pathway that is effective at light-dark condition. Our result is consistent with the conclusion of a previous study in which they adopted a different approach for rhythmicity analysis (35) and also with the finding of a recent study showing continuous-dark specific oscillation in the liver of mice (44) We also observed the same phenomenon with the oscillating AS and APA events: some events became rhythmic only under constant light, and the oscillation profiles of AS and APA events dramatically altered with the change of light regimen. All these suggest that plants organize genome-wide transcriptional and posttranscriptional oscillation according to the timing and duration of light and dark periods.…”
Section: Discussionsupporting
confidence: 93%
“…So, our results suggest that there are two subgroups of circadian genes: one group with oscillation behavior both at light-dark condition and continuous light are only regulated by core clock mechanism, while the other group with continuous light-specific oscillation are regulated by core clock mechanism and also by another pathway that is effective at light-dark condition. Our result is consistent with the conclusion of a previous study in which they adopted a different approach for rhythmicity analysis (35) and also with the finding of a recent study showing continuous-dark specific oscillation in the liver of mice (44) We also observed the same phenomenon with the oscillating AS and APA events: some events became rhythmic only under constant light, and the oscillation profiles of AS and APA events dramatically altered with the change of light regimen. All these suggest that plants organize genome-wide transcriptional and posttranscriptional oscillation according to the timing and duration of light and dark periods.…”
Section: Discussionsupporting
confidence: 93%
“…The expression and activity of circadian proteins are determined by two distinct but complementary and tightly interconnected inputs. On the one hand, an intrinsic cycling related to the circadian clock machinery, exemplified by the fact that mice kept in constant darkness still exhibit clock cycling in the liver [104] and, on the other hand, the dietary status i.e. the feeding/fasting behavior.…”
Section: Temporal Components Of Ppar Regulation A) Hepatic Rhythmic Biologyfeeding State and The Circadian Clockmentioning
confidence: 99%
“…As one of the most widely used lipid‐lowering drugs, simvastatin (SV) inhibits enzymatic activity of hydroxymethylglutaryl coenzyme A reductase ( Hmgcr ), 6 which is rhythmically expressed in the mouse liver 7 . Conflicting statements exist in clinical research about the proper timing of SV administration.…”
Section: Introductionmentioning
confidence: 99%